An Investigation and Design of Networked Learning in Inner-City Leeds - Barker, Tim; Pilkington, Rachel (Proceedings of the International Conference on Networked Learning, 2000)
A pedagogical framework for the implementation of a World Wide Web based course at an inner city Leeds school is described together with a detailed study of students own summarisation of course notes contained therein. Results of this study lead to some recommendations, principally that an artificial Learning Companion would help with the summarisation process, a feature which is lacking with the present support tool. Finally, an overview of a preliminary design for such a Learning Companion is presented as future work.